Comparison of cervical length measured by POP-Q C-D and MRI: Why is POP-Q C-D not accurate?. (January 2020) - Tang, Lian; Liao, Kedan; Jiang, Wenxuan; Feng, Jie; Liu, Ping; Chen, Chunlin
Abstract: Objective: To investigate the relationship between the cervical length evaluated by Pelvic Organ Prolapse Quantification (POP-Q) point C minus D (C–D; ECL) and the magnetic resonance imaging (MRI)-based cervical length (MCL). Study design: This was a retrospective study of patients with POP II-IV who underwent MRI. The ECL was calculated based on the absolute value of C–D according to POP-Q. The MCL was defined as the distance between the internal and external cervical os on MRI. Intraobserver reliability using the Bland-Altman method. Continuous variables were compared by paired 2-tailed t -tests. Multiple linear regression analysis was used to analyse the factors influencing differences between the ECL and MCL. Results: Among 105 eligible patients, 89 patients were eventually included in the study. The Bland-Altman scatter plots show that the intraobserver reliability of MCL was excellent. Furthermore, the mean ECL was significantly longer than the mean MCL (48.15 mm ± 27.46 vs. 28.25 mm ± 10.27, P = 0.000).Body mass index, parity, menopausal status or total vaginal length did not affect the difference between ECL and MCL. However, The larger the point Ba, the larger the difference between the ECL and MCL. The larger the point Bp, the smaller the difference between the ECL and MCL. Conclusion: In general, POP-Q C–D was longer than the cervical length measured by MRI. Deep analysis found that when uterine prolapse is combined with larger anterior vaginal wall prolapse, the difference between ECL and MCL is greater; when uterine prolapse with larger posterior vaginal wall prolapse, the difference between ECL and MCL is smaller.